Pengalaman Beragama; Keharmonisan dan Minoritas dalam Masyarakat Suku Muslim Akit Siak Riau-Indonesia - Abd Madjid; Santoso Santoso; M. Ridwan (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2021)
This article aims to examine the forms of religious experience of the ummah when Muslims live as a minority. Through a sociological approach, qualitatively, this study conducted by observations and in-dept interviews with key figures about religiosity, tolerance, and harmonious relations between religions. The results of the study found that Penyengat Village maintains the religious freedom of its people, and customary stakeholders uphold the principles of togetherness and tolerance. The condition of religious development in the religious community is going well. Under customary protection holders and local governments, Muslim minorities living in a multicultural society can enjoy the freedom and live in harmony